DETECTION OF WEEK ZONE IN EXISTING RCC STRUCTURE SUBJECTED LOAD IN THE FORM OF AN ADDITIONAL STOREY AND CONSIDERATION OF SEISMIC FORCES (International Journal of Engineering Sciences & Management Research, 2017)
All over the world there are plenty of buildings which are vulnerable to damage or damaged by earthquake. There are many buildings which are either designed without consideration of seismic forces or need to be designed with consideration of revised code of earthquake. There are many buildings with the passage of time they realize that their demands have increased and there is a need for the addition/alteration of the current structure. This demand can be fulfilled by constructing a new storey or modification of structure. However, provision for additional load due to the new construction over existing structure was not made in the structural design of the old structure. All such buildings are needed to be retrofitted for additional forces developed due to consideration of new storey and earthquake loads. It represents an opportunity to improve the overall performance of an existing building. The present study investigates the structural performance of G+3 Commercial building under the additional load in the form of new storey and seismic forces. The structure is analyzed for two load cases. In first case structure is analyzed for only gravity forces and no seismic force is considered in this analysis while in second case structure is analyzed with consideration of seismic forces along with gravity forces of G+4 building. The analysis is performed by using structural analysis software i.e. STAAD Pro. The analysis results of structure for gravity load cases STR-GR and seismic load cases STR-EQ are compared to evaluate the effect of seismic forces on the structure. The results point out that the significant increase is found in the shear force and bending moment in most of the beams. This increase of forces is more considerable in plinth beams compared to roof beams. Similarly seismic forces causes increase in bending moment mainly in the columns. The weak and deficient members are identified and strengthened for the additional forces and moments. The strengthening of beams is done by connecting steel plates in the beams with shear connectors and the columns are strengthened by steel angles section and battens.